Meningkatkan Kompentensi Pengelola Wisata Desa melalui Penyuluhan Pelayanan Prima - Hary Hermawan (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2020)
Increasing Competency of Village Tourism Managers through Counseling Prime Services. Customer satisfaction is the key to winning business competition today, including the tourism business. But in the field, there are still many tourism people who still ignore this at this time. A phenomenon that is often encountered is cheating in business, attracting prices too high to achieve big profits in a short time. Therefore, it is very important to do counselling on how to manage good tourism services with a 5-dimensional approach to excellent service, especially for prospective tourism destinations that will develop. To find out the effectiveness of this program, a descriptive analysis has been carried out. The test results indicate there is an understanding of participants about excellent service after counselling.